Decrease of Staphylococcus aureus Virulence by Helcococcus kunzii in a Caenorhabditis elegans Model - Ngba Essebe, Christelle; Visvikis, Orane; Fines-Guyon, Marguerite; Vergne, Anne; Cattoir, Vincent; Lecoustumier, Alain; Lemichez, Emmanuel; Sotto, Albert; Lavigne, Jean-Philippe; Dunyach-Remy, Catherine (Frontiers in Cellular and Infection Microbiology, 2017)
Social bacterial interactions are considered essential in numerous infectious diseases, particularly in wounds. Foot ulcers are a common complication in diabetic patients and these ulcers become frequently infected. This infection is usually polymicrobial promoting cell-to-cell communications. Staphylococcus aureus is the most prevalent pathogen isolated. Its association with Helcococcus kunzii, commensal Gram positive cocci, is frequently described. The aim of this study was to assess the impact of co-infection on virulence of both H. kunzii and S. aureus strains in a Caenorhabditis elegans model. To study the host response, qRT-PCRs targeting host defense genes were performed. We observed that H. kunzii strains harboured a very low (LT50: 5.7 days ±0.4) or an absence of virulence (LT50: 6.9 days ±0.5). In contrast, S. aureus strains (LT50: 2.9 days ±0.4) were significantly more virulent than all H. kunzii (P<0.001). When H. kunzii and S. aureus strains were associated, H. kunzii significantly reduced the virulence of the S. aureus strain in nematodes (LT50 between 4.4 and 5.2 days; P<0.001). To evaluate the impact of these strains on host response, transcriptomic analysis showed that the ingestion of S. aureus led to a strong induction of defense genes (lys-5, sodh-1 and cyp-37B1) while H. kunzii did not. No statistical difference of host response genes expression was observed when C. elegans were infected with either S. aureus alone or with S. aureus + H. kunzii. Moreover, two well-characterized virulence factors (hla and agr) present in S. aureus were down-regulated when S. aureus were co-infected with H. kunzii. This study showed that H. kunzii decreased the virulence of S. aureus without modifying directly the host defense response. Factor(s) produced by this bacterium modulating the staphylococci virulence must be investigated.